Nano and mesosized selenium and its synthesis using the ascorbic acid route - Štefanková, Daniela; Skrbek, Kryštof; Pižl, Martin; Bartůněk, Vilém (Journal of non-crystalline solids, 2023)
•Elemental selenium particles.•Reaction of sodium selenite and ascorbic acid.•Adjusting of pH, HCl addition.•XRD, Uv-Vis, SEM and TEM characterization.•Particles, nanoparticles and networks of Se. Elemental selenium particles have undergone extensive research in recent years. They are interesting for their catalytic, antimicrobial, and many other properties which make them potentially useful in various applications. Despite the widespread research, there are still some information blank spots in the preparation of these nano- and mesosized objects by using a simple reduction reaction between sodium selenite and ascorbic acid without any stabilizing agents which could unpleasantly affect their natural characteristics. This work aimed to prepare these particles and characterize them in the dependence on the reaction mixture composition and pH. Firstly, the reaction system was monitored, in detail, by UV–VIS spectroscopy and a possible deviation in the detection of individual spectral peaks was detected. Furthermore, it is observable that the reaction becomes faster when lowering pH of the reaction mixture. The prepared particles were well-purified and characterized by X-ray powder diffraction, scanning electron, and transmission electron microscopy, where their morphology was observed. The size distribution of the particles was measured by dynamic light scattering and was ranging between 65 and 159 nm. Finally, the dependence of the sample forms on storage time was monitored. It has been shown that the individual objects maintain their primary structure and form, when stored in water, on contrary, dried particles undertook a significant structure and color-change, while forming crystalline polymorphs of gray selenium.